An approach to the design of financial instruments for food system projects - Rogozinski, Jacques; Moncada, Nelly Ramírez (International Food Policy Research Institute, 2021)
This article collects a series of recommendations and experiences from multilateral banks, in particular from the Inter-American Investment Corporation in the period 2005-2013 for the financing of regional projects and the Development Bank in Mexico (2014-2018). Similarly, general considerations are provided for the design and implementation of innovative, flexible and balanced financing schemes between profitability and development in vulnerable sectors such as the food system.